Effectiveness of E-Assessment in Science Learning: Improving the Quality and Efficiency of Assessment in the Digital Era - Rexford Baah; Oleksandr Konovalov; Sangay Tenzin (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The aim of this research is to provide an overview of how effective the use of e-assessment is in science learning. Methodology: This research is qualitative research with a literature review research method. The data in this research is secondary data where data is obtained from search results for documents related to the research topic. The sample from this research in the form of articles was selected based on several criteria, including publications in journals ranging from 2017-2022. After articles that match the topic and the basis of the data are collected, the researcher then carries out a review using several criteria explained in the descriptive statistics table. Main Findings: Based on the results of a review of several relevant articles, it was found that the use of e-assessment will greatly simplify the assessment process and is useful for quickly providing results for science assessment. So the application of e-assessment for assessing student science is very necessary to be implemented in schools. Novelty/Originality of this study: The novelty lies in its focus on the comprehensive application of e-assessment in evaluating cognitive, affective, and psychomotor aspects of science learning. The results of this research can be a basis for policy makers in developing and implementing e-assessment systems in schools. With evidence that e-assessment can speed up the assessment process and improve learning outcomes, policies that support the digitalization of assessments will be more easily accepted.